Porażenie międzyjądrowe mięśni zewnątrzgałkowych w przebiegu stwardnienia rozsianego i urazu głowy. Opis 2 przypadków - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Internuclear ophthalmoplegia (INO) is produced by a lesion in the brainstem involving the medial longitudinal fasciculus (MLF), between the oculomotor and abducens nuclei. This lesion is mostly causes by multiple sclerosis, and only rarely by head injury. INO is a common cause for diplopia in clinical practice. Authors present 2 cases of unilateral internuclear ophthalmoplegia as an isolated sequels of multiple sclerosis and head trauma. They discuss patho-mechanism and diagnostic problems, especially magnetic resonance imaging of MLF lesion.